The level of speeific endurance and technical and tactical efficiency of young football players of different level of competition - Stojanovic, T.; Goranovic, S.; Sakanovic, A.; Stojanovic, D. (Sports Science and Health, 2015)
In order to determine at which level is the specific performance and technical and tactical efficiency of young players of different level of competition, and whether the level of competition can be an indicator of level differences of these abilities, a research was conducted on the sample of young football players aged 14 to 16 from the eight clubs, half of them competing in the higher and the other half in the lower level of competition. A sample of measuring instruments consisted of 13 tests for evaluation of five factors of specific endurance: starting endurance, stamina in maintaining the shallow formation, endurance during fast dribbling, ball pressing endurance, and evaluation of technical and tactical efficiency of football players. The results of the research showed that the young players of higher level of competition had significantly greater technical and tactical efficiency, as well as specific performance in tests which included curvilinear movement and dribbling, as well as control and passing the ball in motion, but the difference is not recorded with straight-line movements and sprints